2011
DOI: 10.1088/0031-9155/56/15/013
|View full text |Cite
|
Sign up to set email alerts
|

Dose verification for respiratory-gated volumetric modulated arc therapy

Abstract: A novel commercial medical linac system (TrueBeam™, Varian Medical Systems, Palo Alto, CA) allows respiratory-gated volumetric modulated arc therapy (VMAT), a new modality for treating moving tumors with high precision and improved accuracy by allowing for regular motion associated with a patient's breathing during VMAT delivery. The purpose of this work is to adapt a previously-developed dose reconstruction technique to evaluate the fidelity of VMAT treatment during gated delivery under clinic-relevant period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…No trend is seen with PTV volume, for volumes ranging from 60 cc to 2388 cc. Our study was based on actual patient breathing traces, while most previous studies 7 , 11 , 13 used a sinusoidal breathing pattern, which may mask problems associated with realistic breathing patterns. These previous studies also used a phase gating approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No trend is seen with PTV volume, for volumes ranging from 60 cc to 2388 cc. Our study was based on actual patient breathing traces, while most previous studies 7 , 11 , 13 used a sinusoidal breathing pattern, which may mask problems associated with realistic breathing patterns. These previous studies also used a phase gating approach.…”
Section: Discussionmentioning
confidence: 99%
“…Riley et al (13) found three out of ten VMAT SABR cases failed the 3%/3 mm gamma test when using realistic patient breathing traces. Qian et al (7) observed gamma passing rates >95% using only sinusoidal breathing traces for VMAT plans delivered on a TrueBeam linac. Similar dosimetric results were reported by Oliver et al (11) for IMRT plans delivered on a Varian 2100 C/D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These files record the position of each MLC leaf throughout the delivery as measured by the MLC motor encoders and have been used extensively for MLC position testing 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Other studies have extended this further and used DynaLog log files to relate the actual MLC position to the dose delivered to patient for IMRT and VMAT patient‐specific QA and delivery verification 21 , 22 , 23 , 24 . Schreibmann et al (23) used DynaLog‐recorded MLC positions to create a DICOM‐compliant plan which could be imported into the treatment planning system to perform a 3D dose reconstruction.…”
Section: Introductionmentioning
confidence: 99%